(untitled) (Research, Society and Development, 2021)
Parkinson’s Disease is a neurodegenerative disorder with a great global impact and, despite recent advances, it still needs improvement in the methods for assessing motor alterations. This study aimed at evaluating a system (hardware and software) capable of accurately quantifying tremor in patients with Parkinson’s disease that underwent pallidotomy. The Mean Absolute Value (MAV) of the involuntary activity of three patients that underwent pallidotomy surgery - in the pre and postoperative scenarios- was evaluated. The Mean Absolute Value of involuntary activity obtained through the suggested device (TREMSEN) showed a good correlation with the clinical findings, as well as with the findings already described in previous studies. The present study showed that MAV alterations were always positively related to tremor, or negatively related to bradykinesia and rigidity, or possibly both. A tendency towards greater tremor influence on the MAV than bradykinesia and rigidity was also observed. The positive correlation among the values measured by the TREMSEN device and the patients´ clinical result opens doors for the future application of technology, such as accurate and objective assessment of motor disorders, continuous monitoring and remote monitoring.